Optimasi dan Karakterisasi Kinerja Sistem Pengukuran Potensiometrik Fosfat dengan Elektroda Kobalt Secara Flow Injection Analysis - Putri F. Rianasari; Zulfikar Zulfikar; Siswoyo Siswoyo (Universitas Batanghari Jambi, 2023)
Phosphorus is known as an essential nutrient required by plant in large numbers and absorbed in the form of phosphate ions, either as a primary orthophosphate ion H2PO4- or secondary orthophosphate ion HPO42-. Concentration of the phosphorus in the soil is usually determined by the spectrophotometric method, while the potentiometric method has not been widely used because of the availability of the phosphate-selective electrodes are not yet available in the market. This research has been conducted in the development and assessment of performance of the potentiometric method that utilizes cobalt metal in the quantitative determination of the phosphate ions in the flow system. Firstly it was performed optimization of pH and concentration of the used buffer solution and the flow rate of the solution to obtain the optimum response of the cobalt electrode in the presence of phosphate ions. It was then followed by an evaluation of the working performance of the flow injection potentiometry method and an interference test of some solutions that are commonly used as a solvent extractors of soil samples. The result showed that the optimum system was achieved when the buffer solution was set to pH 4 at concentration of 1 x 10-3 M and at the flow rate of 2 mL/minute. According to the characterisation results of the method in the process of phosphate determination, the method has a linearity of 0.99, detection limit of 4.86 x 10-5 M, sensitivity of 22.569 mV / decade and precision of â‰¤ 5%.